Nanoemulgel Formulation of Marjoram (Origanum majorana L.) Essential Oil with Potential as Anti-Inflammatory and Anti-Hyperuricemia - Ungsari Rizki Eka Purwanto; Mighfar Syukur; Tris Harni Pebriani; Anissa Nursofiatun (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2024)
The prevalence of hyperuricemia has increased in several countries, including Indonesia. Uric acid will continuously be deposited in the form of crystals in the joint cavity, which can cause inflammation. One natural ingredient potentially treating this problem is marjoram essential oil (Origanum majorana L.). Marjoram essential oil (MEO) contains various terpene compounds that have the potential to reduce pro-inflammatory mediators and uric acid levels. Terpene compounds are known to be able to be delivered through the skin, but their penetration levels are still very limited. The development of pharmaceutical preparations such as nanoemulgel is needed to enhance the penetration of the active components in marjoram essential oil. This research aimed to optimize the components that make up nanoemulgel, namely polysorbate 80 surfactants and PEG 400 co-surfactant, to produce a nanoemulgel preparation of marjoram essential oil with optimum physical characteristics and potential as an anti-inflammatory and anti-hyperuricemia in the rat. The optimum composition of Polysorbate 80 surfactant and PEG 400 co-surfactant is 9.958: 6.042. It resulted in the optimal formula for MEO 1% nanoemulsion, which had an average globule size of 22.94 nm with a polydispersity index of 0.65 and MEO 2% nanoemulsion: 142.4 nm with a polydispersity index of 0.91. MEO nanoemulsion could be dispersed into a gel base and become an MEO nanoemulgel, which has inhibitory power against xanthine oxidase, whereas 2% MEO nanoemulgel has an IC 50 of 25.30+2.57 ppm and has greater anti-inflammatory power than 1% MEO nanoemulgel.